Formulae, Wordplay, Verses and More: Where Humor Research Meets Phraseology - Masiulionytė, Virginija (Kalbotyra, 2020)
This paper aims to examine the meeting points between phraseology and humor research, focusing on the role and the functions of fixed phrases in humor discourse. The examples to illustrate certain aspects of usage of fixed phrases for joke purposes are taken mainly from social media such as Facebook and Twitter and include jokes in English, German, Lithuanian, Russian, and Polish. In the course of the investigation, a distinction ought to be made between set phrases (idioms in the narrower sense of the term, proverbs, catch phrases etc.) and fixed phrases in general. Set phrases (phrasemes) have an “added value” regarding their meaning – be it a figurative element, be it ready-made reasoning or behavioral models in short form in the case of adages. In humor discourse idioms – and proverbs – are used mainly for wordplay, in which both the literal and the idiomatic meaning are activated. The wordplay can happen also in verse form. Adages can be transformed or twisted resulting in new parodistic or funny sayings. Fixed phrases outside of the phraseology can be separated into two groups: phrases typical for a particular discourse type and joke frame related phrases. The former, as means to evoke a certain frame, are used in parodistic jokes (e.g., the phrase ladies if he evokes the dating tips frame). The latter constitute a distinct class of fixed phrases which can be found only in the humor discourse: these phrases act as joke formulae und provide a basis for bigger or smaller joke categories. Certain phrases in this group, such as checks notes or nothing like deserve a mention as irony markers with a distinctive evaluative character. The shared feature of all these idiomatic and non-idiomatic phrases is that they are well-known, re-occur in the language and, in that respect, can considered belonging to the sphere of interests of phraseology. Regarding the main functions of fixed phrases in the humor discourse, they can contribute to the social play, provide the cues to switch to a nonserious humor mindset or express evaluation – from mild mockery to aggressive ridicule.